PENYELESAIAN PEMBIAYAAN MURĀBAHAH BERMASALAH DI BMT MIKAT AL-KHIDMAH PURWOREJO - Muhajir; Fathudin; Hary Listyadi (Al-Mubin, 2021)
The existence of financing is problematic because many partners / customers get stuck in making payments. This problematic financing at BMT Mikat Al-Khidmah Purworejo is not an ordinary problem, and it needs serious handling from BMT Mikat Al-Khidmah. Therefore, the researcher took this title with the aim of wanting to know how the handling of problematic financing was carried out by BMT Mikat Al-Khidmah and how the Islamic Law views the handling methods carried out by BMT Mikat Al-Khidmah. This research is a type of field research (field research) by taking the object of research at BMT Mikat Al-Khidmah Purworejo. Data sources consist of primary and secondary data. Primary data is obtained directly through observation, interviews and documentation. Meanwhile, secondary data is further information relating to research problems from the literature or previous research. Data collection methods used in this research are observation, interview, and documentation methods. Furthermore, data analysis using descriptive analysis method, namely analyzing the data that has been collected and then analyzed to determine the handling of problematic Murābahah financing at BMT Mikat Al-Khidmah